Comprehensive Analysis of mRNA, lncRNA, circRNA, and miRNA Expression Profiles and Their ceRNA Networks in the Longissimus Dorsi Muscle of Cattle-Yak and Yak - Huang, Chun; Ge, Fei; Ma, Xiaoming; Dai, Rongfeng; Dingkao, Renqing; Zhaxi, Zhuoma; Burenchao, Getu; Bao, Pengjia; Wu, Xiaoyun; Guo, Xian; Chu, Min; Yan, Ping; et al. (Frontiers in Genetics, 2021)
Cattle-yak, as the hybrid offspring of cattle (Bos taurus) and yak (Bos grunniens), has obvious heterosis in production performance. Male hybrid sterility has been focused for a long time, however, the mRNAs and non-coding RNAs related to muscle development and their regulatory networks are still unclear. The phenotypic data showed that the production performance (i.e. body weight, withers height, body length, chest girth) of cattle-yak was significantly better than that of yak, and the economic benefits of cattle-yak were higher under the same feeding conditions. Then, we detected the expression profiles of longissimus dorsi muscle of cattle-yak and yak to systematically reveal potential role by high-throughput sequencing technology. Here, 7126 mRNAs, 791 lncRNAs and 1057 circRNAs were identified (P <0.05, |log2FoldChange| >1). These mRNAs, lncRNA targeted genes and circRNA host genes were significantly enriched in myoblast differentiation and some signaling pathways related to muscle development (such as HIF-1 signaling pathway, PI3K-Akt signaling pathway, etc.). We constructed competing endogenous RNA (ceRNA) network and found that some non-coding RNAs differentially expressed may be involved in the regulation of muscle traits. Taken together, this study may be used as a reference tool to provide molecular basis for the study of muscle development.